Dl-NBP (Dl-3-N-Butylphthalide) Treatment Promotes Neurological Functional Recovery Accompanied by the Upregulation of White Matter Integrity and HIF-1α/VEGF/Notch/Dll4 Expression - Wang, Yanping; Shen, Yufei; Liu, Ziyun; Gu, Jingxia; Xu, Congying; Qian, Shuxia; Zhang, Xiaoling; Zhou, Beiqun; Jin, Yuhua; Sun, Yanyun (Frontiers in Pharmacology, 2020)
Dl-3-N-butylphthalide (NBP) has been used in clinic to treat acute ischemic stroke, however, it has not been approved to treat stroke patients during the late stage of ischemic stroke since the effect on functional recovery is not confirmed and the mechanism is not clear. In this study, using mice MCAO model, we aim to explore the effect of two-week NBP treatment on functional recovery after ischemic stroke as well as the underlying mechanism. Our results showed that NBP treatment attenuated improved neurological scores, enhanced the performance in the adhersive remove test, and improved the integrity of white matter after 60-min ischemia and 14-day reperfusion. In addition, NBP increased the number of RECA-1 positive microvessels and enhanced the expression of tight junction protein occludin. More important, NBP also promoted the expression of hypoxia-induced factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), Notch and Delta-like ligand 4 (Dll4). In conclusion, our results showed that NBP treatment promoted the expression of HIF-1α, VEGF, Notch and Dll4, induced angiogenesis, and improved functional recovery 14 day after ischemia/reperfusion. Our results suggested that in future, NBP may also be applied in clinic to promote functional recovery during the later phase of ischemic stroke.